****************** Oscillatory motion ****************** .. include:: macros.rst In order to motivate a more general solution to systems which involve oscillatory motion, first consider the *double pendulum* in which a mass is suspended on a chain of two conjoined pendula. The Double Pendulum =================== .. tikz:: A double pendulum. \draw (0,0) circle (0.1); \draw (0,0) -- (0,-1); \draw (0,-1) -- (1,-2); Consider a double pendulum, consisting of two bobs, one hung below the other. Each has length :math:`a`, and bobs of mass :math:`m`, so the potential energy is .. math:: \PHenergy[V] = -\CMmass \CMg \CMdistance[a] \cos(\theta) - \CMmass \CMg \CMdistance[a] \left( \cos(\theta) + \cos(\phi) \right) and the kinetic energy is .. math:: \PHenergy[T] = \half \CMmass a^2 \ddt{\theta}^2 + \half \CMmass a^2 \left( \ddt{\theta} + \ddt{\phi} \right)^2 Then, .. math:: \begin{aligned} L & = \half \CMmass a^2 \dot{\theta}^2 + \half \CMmass a^2 (\dot{\theta}^2 + \dot{\phi}^2 + 2 \dot{\theta} \dot{\phi}) + \CMmass \CMg \CMdistance[a] (2 \cos(\theta) + \cos(\phi) ) \\ &\approx \half \CMmass \CMdistance[a]^2 \dot{\theta}^2 + \half \CMmass \CMdistance[a]^2 (\dot{\theta}^2 + \dot{\phi}^2 + 2 \dot{\theta} \dot{\phi}) - \CMmass \CMg \CMdistance[a] \left(\theta^2 + \half \phi^2 \right) \end{aligned} The equations of motion from the Lagrange equations are .. math:: \begin{aligned} 2 \ddot{\theta} + \ddot{\phi} + \frac{2 \CMg}{a} \theta & =0 \\ \ddot{\theta} + \ddot{\phi} + \frac{\CMg}{a} \phi &= 0 \end{aligned} Each of these equations has a form comparable to that of a harmonic oscillator, :math:`\ddot{x} + \omega^2 x = 0`; attempting a trial solution .. math:: \begin{bmatrix} \theta \\ \phi \end{bmatrix} = \begin{bmatrix} c_{\theta} e^{i \omega t} \\ c_{\phi} e^{i \omega t} \end{bmatrix} For :math:`c_{\theta}`, :math:`c_{\phi}` complex constants, then .. math:: \ddot{\theta} = - \omega^2 \theta, \qquad \ddot{\phi} = - \omega^2 \phi So .. math:: \begin{aligned} \label{eq:39} \qty( - 2 \omega^2 + \frac{2g}{a} ) c_{\theta} - \omega^2 c_{\phi} &= 0 \\ \label{eq:38} - \omega^2 c_{\theta} + \qty( -\omega^2 + \frac{g}{a} ) c_{\phi} &= 0 \end{aligned} Which can be expressed in matrix notation .. math:: \label{eq:37} \begin{bmatrix} 2 \frac{g}{a} - 2 \omega^2 & - \omega^2 \\ - \omega^2 & \frac{g}{a} - \omega^2 \end{bmatrix} \begin{bmatrix} c_{\theta} \\ c_{\phi} \end{bmatrix} = 0 This implies that the determinant of the matrix must be zero, so .. math:: \label{eq:40} \begin{vmatrix} 2 \frac{g}{a} - 2 \omega^2 & - \omega^2 \\ - \omega^2 & \frac{g}{a} - \omega^2 \end{vmatrix} = 2 \qty( \frac{g}{a} - \omega^2 )^2 - \omega^4 = 0 This has two solutions, .. math:: \label{eq:41} \omega^2 = \frac{g}{a} ( 2 \pm \sqrt{2}) which are the normal frequencies for the system, and the coordinates :math:`c_i` are the normal modes. To find these we substitute the normal frequencies into equation, .. math:: \label{eq:42} \frac{g}{a} \begin{bmatrix} 2-4-2 \sqrt{2} & -2-\sqrt{2} \\ -2 -\sqrt{2} & 1-2-\sqrt{2} \end{bmatrix} \begin{bmatrix} c_{\theta} \\ c_{\phi} \end{bmatrix} = 0 These turn out to give two copies of the same equation relating the coefficients, so clearly only the relative relation of them is fixed, .. math:: \label{eq:43} \frac{c_{\theta}}{c_{\phi}} = - \frac{2 + \sqrt{2}}{2(1+\sqrt{2})} = - \frac{(2+\sqrt{2})(1-\sqrt{2})}{2(1+\sqrt{2})(1-\sqrt{2})} = -\frac{1}{\sqrt{2}} Thus .. math:: \begin{bmatrix} c_{\theta} \\ c_{\phi} \end{bmatrix} \propto \begin{bmatrix} -1 \\ \sqrt{2} \end{bmatrix} and using the negative solution .. math:: \begin{bmatrix} c_{\theta} \\ c_{\phi} \end{bmatrix} \propto \begin{bmatrix} 1 \\ \sqrt{2} \end{bmatrix} Giving a general solution .. math:: \begin{bmatrix} \theta \\ \phi \end{bmatrix} = \alpha_1 \begin{bmatrix} -1 \\ \sqrt{2} \end{bmatrix} e^{i \omega_1 t} + \alpha_2 \begin{bmatrix} 1 \\ \sqrt{2} \end{bmatrix} e^{i \omega_2 t} This can be rewritten in matrix form too, .. math:: \label{eq:46} \begin{bmatrix} \theta \\ \phi \end{bmatrix} = \begin{bmatrix} - 1 & 1 \\ \sqrt{2} & \sqrt{2} \end{bmatrix} \begin{bmatrix} \alpha_1 e^{i \omega_1 t} \\ \alpha_2 e^{i \omega_2 t} \end{bmatrix} This can be inverted, giving .. math:: \label{eq:47} \begin{bmatrix} \alpha_1 e^{i \omega_1 t} \\ \alpha_2 e^{i \omega_2 t} \end{bmatrix} = \begin{bmatrix} - \half & \half \sqrt{2} \\ \half & \half \sqrt{2} \end{bmatrix} \begin{bmatrix} \theta \\ \phi \end{bmatrix} = \begin{bmatrix} \xi_1 \\ \xi_2 \end{bmatrix} For :math:`\xi_i` the *normal coordinates* of the system, these cause the Lagrange equations to completely decouple. General Theory of Small Oscillations ==================================== Consider a system with time-independent constraints; this is in equilibrium if .. math:: \pdv{V}{q_i} = 0 Furthermore, a stable equilibrium has .. math:: \pdv[2]{V}{q_i}{q_j} > 0 \quad \forall i, j Denoting the equilibrium value of each coordinate :math:`q^{*}_i`, we can introduce a small perturbation, :math:`\eta_i`, such that .. math:: \label{eq:48} q_i = q^{*}_i + \eta_i Assuming small displacements we can use Taylor’s theorem to expand the potential about :math:`q_i = q_i^{*}`: .. math:: \label{eq:49} V = V^{*} + \sum \eta_i \pdv{V}{q_i} + \sum_{i,j} \half \qty( \pdv[2]{V}{q_i}{q_j} ) \eta_i \eta_j to the second-order. The potential thus has the form of the second derivative term, .. math:: \label{eq:50} V = \sum_{i,j} \half V_{,ij} \eta_i \eta_j Using the comma notation for derivatives. The matrix :math:`\mat{V}` has components :math:`V_{,ij}`, and the set of displacements :math:`\eta_i` forms a vector :math:`\vec{\eta}`, so .. math:: \label{eq:51} V = \half \trans{\eta} \mat{V} \eta Since :math:`\mat{V}` doesn’t depend upon the coordinates, just the equilibrium values, it is constant. The kinetic energy has the form .. math:: \label{eq:52} T = \sum_{i,j} \half m_{ij} \dot{q}_i \dot{q}_j Expanding about the equilibrium we find .. math:: \dot{q}_i = \dot{\eta}_i and .. math:: m_{ij}(q_1, \dots, q_n) = m_{ij}(q_1^{*}, \dots, q_n^{{*}}) + \cdots Then .. math:: \label{eq:53} T = \sum_{i,j} \half T_{ij} \dot{\eta}_i \dot{\eta}_j having defined :math:`T_{ij} = m_{ij}(q^*_1, \dots, q^{*}_n)`, which is a constant matrix, so we have .. math:: \label{eq:54} T = \half \trans{\dot{\eta}} \mat{T} \dot{\eta} and .. math:: \label{eq:55} L = T-V = \sum_{i,j} \half \qty[ T_{ij} \dot{\eta}_i \dot{\eta}_j - V_{ij} \eta_i \eta_j] = \half \trans{\dot{\eta}} \mat{T} \dot{\eta} - \half \trans{\eta} \mat{V} \eta The Lagrange equations have the form .. math:: \dv{t} \pdv{L}{\dot{\eta}_k} = \pdv{L}{\eta_k} Taking this in bits, .. math:: \pdv{L}{\dot{\eta}_k} = \half \sum_{i,j} T_{ij} \qty[ \pdv{\dot{\eta}_i}{\dot{\eta}_k} + \dot{\eta}_i \pdv{\dot{\eta}_j}{\dot{\eta}_k}] The generalised coordinates are independent, so .. math:: \pdv{\dot{\eta}_i}{\dot{\eta}_k} = \delta_{ik} Thus .. math:: \label{eq:56} \pdv{L}{\dot{\eta}_k} = \half \sum_{i,j} T_{ij} \qty[ \delta_{ik} \dot{\eta}_j + \dot{\eta}_i \delta_{jk}] = \sum_j T_{kj} \dot{\eta}_j Similarly, .. math:: \label{eq:57} \pdv{L}{\eta_k} = - \sum_j V_{,kj} \eta_j This gives the Lagrange equations in the form .. math:: \label{eq:58} \sum_j (T_{ij} \ddot{\theta}_j + V_{,ij} \eta_j) = 0 \equiv \mat{T} \ddot{\vec{\eta}} + \mat{V} \vec{\eta}_j = \vec{0} As in the double pendulum case, we can find solutions of the form .. math:: \eta = \vec{c} e^{i \omega t} Then :math:`\ddot{\eta} = - \omega^2 \eta`, and so .. math:: \label{eq:59} \qty( \mat{V} - \omega^2 \mat{T} ) \eta = \vec{0} To satisfy the equation we need .. math:: \label{eq:60} \abs{\mat{V}-\omega^2 \mat{T}} = 0 which is a characteristic equation, and this can be approached as an eigenvalue equation, and once the normal frequencies are found we substitute them back in turn, and find the vectors :math:`\vec{c}` by solving .. math:: \mat{V} \vec{c} = \omega^2 \mat{T} \vec{c} for each :math:`\omega^2`. THis is akin to finding the eigenvectors of a matrix, and the vectors specify the *normal modes* of the oscillation. In general, from the fact that :math:`\mat{V}` and :math:`\mat{T}` are symmetric, and that :math:`\omega^2` has real solutions, that :math:`\vec{c}` can be chosen to be orthonormal. The general solution takes the form .. math:: \label{eq:80} \begin{pmatrix} \eta_1 \\ \vdots \\ \eta_n \end{pmatrix} = \sum_j \alpha_j \vec{c}^{(j)} \exp( i \omega_j t) = \sum_j \alpha_j \begin{pmatrix} c_1^{(j)} \\ \vdots c_n^{(j)} \end{pmatrix} \exp(i \omega_j t) which can be expressed more compactly, using Einstein notation, .. math:: \label{eq:81} \eta_i = c_i^j \alpha_j \exp(i \omega_j t) for :math:`c_i^j = c_i^{(j)}`. We can then define normal coordinates, .. math:: \xi_j = \alpha_j \exp(i \omega_j t) which correspond to the oscillation of the system at a single frequency, and can be found by inverting equation ([eq:80]), so .. math:: \label{eq:82} \xi_j = (c_i^j)^{-1} \eta_i The Lagrangian then completely decouples into the sum of independent harmonic oscillators, .. math:: \label{eq:87} L = \sum_j C_j \qty[ \dot{\xi}_j^2 - \omega^2_j \xi_j^2] for :math:`C_j` a normalisation constant.